Weeds - Edwards, Nina (Reaktion Books Ltd, 2024)
«To most of us, weeds can seem nothing more than intruders in gardens, farms and city streets. But the idea of the weed is a slippery one, constantly changing according to different needs, fashions and contexts. In a well-ordered field of corn, a scarlet poppy is a bright red intruder, but in other parts of the world it is an important cultural symbol, a potent and lucrative pharmaceutical source, or simply a beautiful ornament. Fat hen, which today we consider a pest, was in Neolithic times a staple crop, its seeds an important source of nutrition. Weeds sketches the history of the fashions and attitudes that have shaped our fields and gardens, showing that what we keep out of them is just as fascinating as what we put in.»--Page 4 de la couverture
Keywords: Weeds; Weeds / History; Plants and civilization; Human-plant relationships; Mauvaises herbes; Mauvaises herbes / Histoire; Plantes et civilisation; Relations homme-plante